Early diagnosis of sickle cell anemia: a literature review (Research, Society and Development, 2020)
Sickle-cell anemia (Sickle-cell anemia) is a disease characterized by the presence of abnormal red cells (sickle-shaped) that are removed from the circulation and destroyed by an inherited genetic disorder due to a mutation of the gene encoding the amino acid valine, transcribing an altered hemoglobin. The objective of the research is to verify the main means used for the laboratory diagnosis of sickle cell anemia and the carriers of these traits, as well as to perform an analysis of the literature related to the educational strategies on genetic counselingadded in the Unified Health System (SUS), especially in Attention Basic. An exploratory, descriptive research was carried out through a bibliographic review. The databases consulted were Virtual Health Library - VHL and SciELO - Scientific Electronic Library, where the existence of articles, dissertations, theses related to the subject were verified. It is observed that although there is a vast literature on Sickle Cell Anemia, there is little recent research in the databases used for this research related to the Diagnostics and educational strategies adopted in the Unified Health System (SUS), Anemia and genetic counseling.